Savage son : a thriller - Carr, Jack (Joint pseudonym) (New York : Emily Bestler Books/Atria, 2020)
"Deep in the wilds of Siberia, a woman is on the run, pursued by a man harboring secrets--a man intent on killing her. A traitorous CIA officer has found refuge with the Russian mafia with designs on ensuring a certain former Navy SEAL sniper is put in the ground. Half a world away, James Reece is recovering from brain surgery in the Montana wilderness, slowly putting his life back together with the help of investigative journalist Katie Buranek and his longtime friend and SEAL teammate Raife Hastings. Unbeknownst to them, the Russian mafia has set their sights on Reece in a deadly game of cat and mouse. In his most visceral and heart-pounding thriller yet, Jack Carr explores the darkest instincts of humanity through the eyes of a man who has seen both the best and the worst of it."-- Provided by publisher.
Keywords: United States. -- Navy. -- SEALs -- Fiction; Organized crime -- Fiction; Assassins -- Fiction; Russia -- Fiction; Political fiction; Thrillers (Fiction)